2019
DOI: 10.1029/2018wr023229
|View full text |Cite
|
Sign up to set email alerts
|

Snow Drought Risk and Susceptibility in the Western United States and Southwestern Canada

Abstract: In western North America (WNA), mountain snowpack supplies much of the water used for irrigation, municipal, and industrial uses. Thus, snow droughts (a lack of snow accumulation in winter) can have drastic ecological and socioeconomic impacts. In this study, the historical (1951–2013) frequency, severity, and risk (frequency × severity) of dry, warm, and warm and dry snow droughts are quantified at the grid‐cell and ecoregion scale for snow‐dominated regions in the western United States and southwestern Canad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
83
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(89 citation statements)
references
References 86 publications
6
83
0
Order By: Relevance
“…While several recent studies have focused of snow drought (Dierauer et al, 2019;Mote et al, 2016;Harpold et al, 2017) and its hydrological impacts (Cooper et al, 2016;Sproles et al, 2017;Hatchett and McEvoy, 2018), no previous studies have explicitly related climate change impacts on snow drought to subsequent impacts on summer low flows and summer streamflow drought. In this study, generic GW-SW models of headwater catchments were combined with downscaled climate change projections for two different RCPs.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…While several recent studies have focused of snow drought (Dierauer et al, 2019;Mote et al, 2016;Harpold et al, 2017) and its hydrological impacts (Cooper et al, 2016;Sproles et al, 2017;Hatchett and McEvoy, 2018), no previous studies have explicitly related climate change impacts on snow drought to subsequent impacts on summer low flows and summer streamflow drought. In this study, generic GW-SW models of headwater catchments were combined with downscaled climate change projections for two different RCPs.…”
Section: Discussionmentioning
confidence: 99%
“…In general, snow drought regimes in all catchments shift toward more frequent, higher severity warm, and warm and dry, snow droughts, and less frequent, lower severity dry snow droughts. As documented by Dierauer et al (2019) and shown in Figure S9, the response of warm snow drought risk to increased winter temperature is non-linear. A 2°C increase in the mean winter (1-Nov to 1-Apr) temperature corresponds to a substantially larger increase in warm snow drought risk for the Capilano catchment as compared to the Fort Nelson catchment.…”
Section: Snow Droughtmentioning
confidence: 94%
See 2 more Smart Citations
“…The nonlinearity in snowfall frequency declines over the twenty‐first century suggests that associated impacts will accelerate in future decades without implementation of mitigation strategies, which has implications for short‐term versus long‐term planning. This is particularly important in lower elevation locations, which are more sensitive to changes in temperature (Mote et al, ) and, thus, more susceptible to snow droughts (Dierauer et al, ). Yet even in a stationary climate, the interplay between snowpack and its surrounding environment (e.g., wildfire, canopy density, and slope angle) is integral to water storage.…”
Section: Conclusion and Discussionmentioning
confidence: 99%